Gut Microbiome and Response to Cardiovascular Drugs. (September 2019) - Tuteja, Sony; Ferguson, Jane F.
Abstract : The gut microbiome is emerging as an important contributor to both cardiovascular disease risk and metabolism of xenobiotics. Alterations in the intestinal microbiota are associated with atherosclerosis, dyslipidemia, hypertension, and heart failure. The microbiota have the ability to metabolize medications, which can results in altered drug pharmacokinetics and pharmacodynamics or formation of toxic metabolites which can interfere with drug response. Early evidence suggests that the gut microbiome modulates response to statins and antihypertensive medications. In this review, we will highlight mechanisms by which the gut microbiome facilitates the biotransformation of drugs and impacts pharmacological efficacy. A better understanding of the complex interactions of the gut microbiome, host factors, and response to medications will be important for the development of novel precision therapeutics for targeting CVD.